Public Opinion concerning the Feasibility of South Africa meeting its greenhouse gas emission targets - Davids, Zahraa (School of Economics, 2024)
Climate change and global warming are measurable realities. Developing countries like South Africa are more vulnerable to their impacts due to the country's socio-economic background. The Paris Agreement was adopted to limit the rise of global mean temperatures to 1.5°C above pre-industrial levels. However, with current policy projections and the absence of efficacious mitigation efforts, global temperatures are expected to surpass critical thresholds required for effective climate change management. Thus, achieving lower temperatures would require more ambitious mitigation efforts. The methodology utilized in this dissertation employs a non- random survey of expert opinions on the topic of the feasibility of South Africa meeting its greenhouse gas emission targets. A snowball sampling method was utilized to identify suitable respondents to the survey. The survey reveals about 53% of participants believe that the feasibility of South Africa meeting its emission reduction target by 2030 is quite improbable due to the country's dependence on the coal industry. Participants have expressed concerns about the effectiveness of the country's current carbon tax. They believe it may not lead to the necessary level of emission reductions or foster long-term compliance, primarily due to high tax exemptions and the low level of the carbon tax. Participants argue that enhancing South Africa's mitigation policies should include several mitigation instruments to catalyse emission reduction efforts and facilitate a renewable energy transition which should be done in a just manner. The study shows that expert opinion research could be beneficial for policymakers in advancing climate action. However, achieving this would depend on cooperation and collaboration among a wide array of stakeholders.